Small transition metal cluster adsorbed on graphene and graphene nanoribbons: A density functional based tight binding molecular dynamics study - Mananghaya, Michael Rivera (Animo Repository, 2018)
The systemic study of the electronic properties of different transition metals (TMs-Sc, Ti, Fe, Co, Ni, Zn, Ag and Au) adsorbed in the surface of graphene was done with the aid of self-consistent charge density functional based tight binding method. Results show that the Silver metal adsorbed in the surface of graphene can open its gapless bandstructure. In addition, a single-gated field effect transistor based on Ag-adsorbed on zigzag graphene nanoribbon (zGNR) can act as a potential semiconductor for modern electronic applications. An important feature is that the Ag does not break the structure of zGNR on adsorption. Further, the resulting Ag/zGNR energy band gap is inversely proportional on the dimer lines across its width as predicted by tight-binding calculations. © 2018 Elsevier B.V.